Assessment of Psychological Needs and Quality of Life of Penitentiary Security Agents in the State of Paraíba - Amorim-Gaudêncio, Carmen; da Silva, Sayonara Pereira; Braz, Lucas Felício Gil (Utan Kayu Publishing, 2023)
The Penitentiary Security Agent (PSA) profession can expose individuals to risk, fear, and violence in the workplace, leading to high levels of stress and anxiety that can impact their quality of life. This study evaluated psychological needs and quality of life characteristics of a group of PSAs in Joao Pessoa, Paraiba. Anxiety levels, impulsiveness, and quality of life were evaluated in 64 professionals using various scales. The results showed that anxiety was moderate in men only in the Cognitive and Physiological scales and absent in the Motor and General Level of Anxiety scales. In women, moderate anxiety was observed in all four subscales. Quality of life was rated as regular in all four domains, with Social Relations being the best-structured and Environment being the lowest scoring domain. The evaluation of impulsivity showed a low score in the Lack of Concentration and Persistence factor, an extreme lower score in the Cognitive Control and Future Planning factors, and a medium score in the Audacity and Temerity factor. These results differ from the literature, indicating high anxiety scores and low quality of life for PSAs. Thus, further studies are needed to understand the impact of the work environment on the psyche of PSAs and develop actions to improve their psychological needs, manage anxiety and impulsivity, and positively impact their quality of life.